Weaning food from liquefied starches - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Throughout the developing world boiled starchy grains and roots are given as weaning food to millions of children. Boiled starch is so thick and pasty that it is difficult for the very young to swallow enough to gain adequate nourishment. But the...